2021
DOI: 10.1007/s00421-021-04828-9
|View full text |Cite
|
Sign up to set email alerts
|

The association of elevated blood pressure during ischaemic exercise with sport performance in Master athletes with and without morbidity

Abstract: Background An exaggerated exercise blood pressure (BP) is associated with a reduced exercise capacity. However, its connection to physical performance during competition is unknown. Aim To examine BP responses to ischaemic handgrip exercise in Master athletes (MA) with and without underlying morbidities and to assess their association with athletic performance during the World Master Track Cycling Championships 2019. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 89 publications
0
2
0
Order By: Relevance
“…This is explained by the increased tone of the parasympathetic nervous system and increased sensitivity of baroreceptors. 24 However, prolonged strenuous exercise can potentially lead to cardiovascular dysfunction and hidden hypertension with altered cardiac function, which is an increased risk among veteran athletes. 25 , 26 In addition, veterans who develop predominantly endurance quality (cyclists, runners and swimmers, triathletes) show greater pliability and less vascular wall stiffness, increased endothelial function, improved blood flow, adequate BP regulation at rest and during exercise compared to healthy people of the same age who led a sedentary lifestyle.…”
Section: Discussionmentioning
confidence: 99%
“…This is explained by the increased tone of the parasympathetic nervous system and increased sensitivity of baroreceptors. 24 However, prolonged strenuous exercise can potentially lead to cardiovascular dysfunction and hidden hypertension with altered cardiac function, which is an increased risk among veteran athletes. 25 , 26 In addition, veterans who develop predominantly endurance quality (cyclists, runners and swimmers, triathletes) show greater pliability and less vascular wall stiffness, increased endothelial function, improved blood flow, adequate BP regulation at rest and during exercise compared to healthy people of the same age who led a sedentary lifestyle.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it can be concluded that research on stretching is mostly focused on adolescents and young adults in their most physically active years and when organized sports participation and engagement in physical activity in general are most common [381,382]. Notwithstanding, there has been increased participation in sports by older adults, with rising awareness of the specificity of the master athlete in the sports science literature [383][384][385][386][387][388]. Our scoping review showed that research on stretching in master athletes is largely lacking, and so how these older athletes respond to stretching interventions is currently unclear.…”
Section: Agementioning
confidence: 99%